Performance Evaluation of City Parks Based on Sustainable Landscape Design in Jakarta - Silia Yuslim; Etty Indrawati (Universitas Diponegoro, Indonesia, 2022)
Green open spaces, especially urban parks, are needed by the community and the city to minimize environmental problems and improve life quality. City parks in Jakarta have not been able to do so. The research will evaluate the city parks performance based on sustainable landscape design to see how well city parks have the functions as contained in the 2019 Green Open Spaces Guidelines for Sustainable Development and Development. Previous research has measured the city parks performance as their functions related to ecological, health/quality of life, economic, aesthetic, socio-cultural aspects. This study will add the aspect of mitigation as one of the measurement variables and at the same time as an update of the research. The evaluation instrument uses a questionnaire that contains an evaluation variable for city parks performance that combines all the function aspects of city parks with sustainable landscape design and observation principles. The purpose of this research is to provide evaluation results and recommendations. Performance evaluation based on city parks sustainable landscape design, there is no city parks function applied in good category and observationally, the condition of city parks is poorly maintained and gloomy. The recommendation is further research is needed that utilizes a sustainable landscape design to look for more deeply the root causes factors why the function and sustainability of city parks could not be achieved.